2012
DOI: 10.1007/s00360-012-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, tissue expression pattern and daily rhythms of Period1, Period2, and Clock transcripts in the flatfish Senegalese sole, Solea senegalensis

Abstract: An extensive network of endogenous oscillators governs vertebrate circadian rhythmicity. At the molecular level, they are composed of a set of clock genes that participate in transcriptional-translational feedback loops to control their own expression and that of downstream output genes. These clocks are synchronized with the environment, although entrainment by external periodic cues remains little explored in fish. In this work, partial cDNA sequences of clock genes representing both positive (Clock) and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 69 publications
7
18
0
Order By: Relevance
“…The dark-biased expression of the 3 period genes was in agreement with the expression of other teleost orthologs in central and peripheral tissues such as in goldfish ( Carassius auratus ) [29], European sea bass [10] and zebrafish [19], [38]. On the other hand, this circadian preference is not similar to what has been observed in central and peripheral clocks of Senegalese sole [11]. In the established circadian feedback loop model, the proteins translated by per and cry genes interact to inhibit the transcriptional activation arm [1].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The dark-biased expression of the 3 period genes was in agreement with the expression of other teleost orthologs in central and peripheral tissues such as in goldfish ( Carassius auratus ) [29], European sea bass [10] and zebrafish [19], [38]. On the other hand, this circadian preference is not similar to what has been observed in central and peripheral clocks of Senegalese sole [11]. In the established circadian feedback loop model, the proteins translated by per and cry genes interact to inhibit the transcriptional activation arm [1].…”
Section: Discussionsupporting
confidence: 79%
“…The molecular components of the clock system in a number of aquaculture fish species, such as in European sea bass ( Dicentrarchus labrax ) [10], Senegalese sole ( Solea senegalensis ) [11], rainbow trout ( Oncorhynchus mykiss ) [12] and Atlantic salmon ( Salmo salar ) [13], have also been studied to a limited extent. he Somalian cavefish ( Phreatichthys andruzzii ) provided significant new insights into the evolution and entrainment of circadian clocks.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have explored, under both laboratory and field conditions, how the circadian clock has evolved in this species. In the laboratory, surface fish show a robust circadian oscillation in per1 gene expression, as has been previously reported for zebrafish and other teleost species 20,31,32,34,42 . A high-amplitude per1 rhythm is also apparent in surface fish under natural conditions.…”
Section: Discussionsupporting
confidence: 72%
“…Silico structural analysis of the deduced amino acid sequences indicated that clock and per1 proteins contain the conserved PAS and bHLH domains [24]. These two domains are required for the circadian clock functions and are highly conserved in different species during evolution [25].…”
Section: Discussionmentioning
confidence: 99%